Revisiting the mitogenetic effect of ultra-weak photon emission - Volodyaev, Ilya; Beloussov, Lev V. (Frontiers in Physiology, 2015)
This paper reviews the ninety years long controversial history of the so-called “mitogenetic radiation”, the first case of non-chemical distant interactions, reported by A.Gurwitsch in 1923. It was soon described as ultraweak UV, emitted by a number of biological systems, and stimulating mitosis in “competent” (in this sense) cells. In the following 20 years this phenomenon attracted enormous interest of the scientific community, and gave rise to more than 700 publications around the world. Yet, this wave of research vanished after several ostensibly disproving works in late 1930-s, and was not resumed later, regardless of quite serious grounds for that. The authors discuss separately two aspects of the problem: (1) do living organisms emit ultraweak radiation in the UV range (irrespective of whether it has any biological role), and (2) are there any real effects of this ultraweak photon emission (UPE) upon cell division and/or other biological functions? Analysis of the available data permits to conclude, that UV fraction of UPE should be regarded real, while its biological effects are difficult to reproduce. This causes a paradox. A number of presently known qualities of UPE were initially discovered (predicted?) by the “early workers” on the basis of biological effects. Yet the qualities they discovered were proved later (the UV component of UPE, the sources of UPE among biological systems, etc.), while the biological effect they used for UPE “detection”, remains questionable. Importance of this area for basic biology and medicine, and potential usefulness of UPE as a non-invasive research method, invite scientists to attack this problem again, applying powerful research facilities of modern science. Yet, because of complexity and uncertainty of the problem, further progress in this area demands comprehensive examination of both positive and negative works, with particular attention to their methodical details.